(untitled) (Medico Legal Update, 2020)
Diversity is a part of our everyday lives. Having good attitudes towards LGBT (lesbian, gay, bisexual & transgender) individuals is one of the ways of accepting and respecting human diversity. In this way, the quality of offered services will be same for all the people. Attitudes of medical professionals towards homosexuals can influence their willingness to provide these individuals with medical help. The study evaluates the medical students’ knowledge about homosexuality and their attitudes towards it. The sample consisted of 200 participants (104 from second year & 96 from first year) who anonymously completed the preformed questionnaire. The study showed that the second year students have more knowledge than the first year students. Degree of knowledge had significant predictive effect on attitudes in the analyzed predictive model & is important tool in shaping the attitudes towards LGBT patients and reducing stigmatization.